Flexible labour markets, workers' protection and active labour market policies in the Caribbean - Downes, Andrew S. (UN SantiagoCL, 2009)
Examines the application of flexicurity (labour market flexibilty with social security for workers, originating in Denmark) labour system in the Caribbean countries of Barbados, Jamaica and Trinidad and Tobago. Provides an overview of labour in the three countries and compares their performance with that of Denmark.